A Study on Correlation between Chinese Sentence and Constituting Clauses Based on the Menzerath-Altmann Law. Issue 4 (2nd October 2017) - Hou, Renkui; Huang, Chu-Ren; Do, Hue San; Liu, Hongchao
Abstract: The Menzerath-Altmann law (henceforth the MA law), discovered by Menzerath and formulated by Altmann, describes the correlation between the language structure and its immediate components at all linguistic levels. This paper examines the correlation between Chinese sentences and their components, clauses, in texts from different registers based on the MA law. The results show that the correlation is described by the MA law only in the formal written texts.